2003
DOI: 10.1080/10584580390258282
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Imprint Behavior of PZT Thin Films

Abstract: Ferroelectric thin film capacitors are promising candidates for non-volatile ferroelectric Random Access Memories (FeRAM's) as they exhibit a switchable polarization. There are three important failure-mechanisms influencing the performance of these capacitors and disturbing the long-term stability and reliability under operation conditions fatigue, retention, and imprint. The imprint effect of lead zirconate titanate (PZT) thin films was investigated in this paper. Establishing and maintaining a polarization s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Once polarized, ferroelectric materials become stabilized in the existing poling orientation and resist reversal up to a critical coercive field. [15][16][17] This logarithmic time dependence of the imprint voltage has also been observed in P͑VDF-TrFE͒ films 18 and is shown in Fig. Experimentally, imprint is observed as a shift in the polarization hysteresis curve to higher fields with increasing wait time in a given polarization state, or as an increase in the electric field required to achieve a given polarization switching rate.…”
Section: Introductionsupporting
confidence: 65%
“…Once polarized, ferroelectric materials become stabilized in the existing poling orientation and resist reversal up to a critical coercive field. [15][16][17] This logarithmic time dependence of the imprint voltage has also been observed in P͑VDF-TrFE͒ films 18 and is shown in Fig. Experimentally, imprint is observed as a shift in the polarization hysteresis curve to higher fields with increasing wait time in a given polarization state, or as an increase in the electric field required to achieve a given polarization switching rate.…”
Section: Introductionsupporting
confidence: 65%
“…22, where the voltage shift of the P-E loop as a function of oxygen pressure is shown for a PZT capacitor with oxide electrodes. For an empirical fit of this dependence, different single functions and combination of functions have been used-for instance, a single logarithm function, 80 two logarithm functions with different parameters at small and large times, 90 and a stretched exponential function. Experimental data that can also indicate the role of oxygen vacancies in the formation of built-in field in PZT thin films have been reported on imprint in donor-doped ͑Nb, Ta, and W substitutions for Ti͒ films.…”
Section: Internal Bias Field and Imprint: Theory Versus Experimentmentioning
confidence: 99%
“…In earlier publication, it could be clearly shown that the imprint behavior is not a linear function of the elapsed time ͑on a logarithmic scale͒ as commonly assumed. 8 To achieve a sufficient fit approach, several dependencies were performed and compared by their minima values of nonlinear least squares. So qualitatively, this behavior has to be approximated by a slight exponential growth fit.…”
Section: ͑2͒mentioning
confidence: 99%